Benzimidazopurine nucleosides from N(6)-aryl adenosine derivatives by PhI(OAc)(2)-mediated C–N bond formation, no metal needed - Satishkumar, Sakilam (Chem Commun (Camb), 2017)
The reaction of a variety N(6)-aryl 2’-deoxyadenosine and adenosine derivatives with PhI(OAc)(2) in 1,1,1,3,3,3-hexafluoro-2-propanol provides facile access to benzimidazopurine nucleoside analogues by metal-free C–N bond formation with a purinyl nitrogen atom. These reactions likely proceed via radical-cation/radical processes as indicated by radical inhibition experiments.